Upstream Pre-Intermediate B1: Teacher's Book - Evans V. Virginia (Newbury, Express Publishing, 2008)
"Upstream: Pre-lntermediate B1" is a modular secondary-level course for learners of the English language at CEF B1 level. The series combines active English learning with a variety of lively topics presented in themed units. Key features: theme-based units from a wide variety of authentic sources in five modules, a variety of cross-cultural topics, systematic development of all four language skills through realistic challenging tasks which encourage the learner's personal engagement, lexical exercises practising and activating all essential vocabulary including collocations, idioms, phrasal verbs, fixed phrases and word formation, a varied range of reading texts from authentic contemporary sources, with exercises which encourage learners to read extensively as well as intensively, stimulating reading and listening tasks, a wide range of speaking activities, writing analysis and practice on all types of writing with full models, Self-Assessment sections at the end of each module, grammar sections covering all major grammatical areas and more advanced grammar points plus a Grammar Reference Section, songs.